“Neoprivatisation” in Public Schools in Nepal - Ghimire, Shurendra; Koirala, Kamal Prasad (Journal of Education and Research, 2019)
This article introduces the term “neoprivatisation” in the literature of economics of education. It exposes the consequence of privatisation in education to public school by taking a community as a case and studying in a mixed-method paradigm. The study uncovers that public schools suffer from lesser preference by parents, and underuse or misuse of public expenditure, so that, like private schools, have added the facilities of English medium, extra-class, preparing students for test by charging fees, as well as advertising to attract more students. As a result, the narrow focus to achievement score rather than developing qualities in students as expected by curriculum has threatened the presumption of ‘quality education’; and the commodification and commercialisation of education along with diminishing professional accountability of teacher victimise students with the undue burden of irrational extra-classes and fees. Therefore, the added facilities rouse for discriminating students in access to education and larceny of ‘right to free education’. These undesirable phenomena are the consequences of privatisation in education, which has been thus conceptualized as “neoprivatisation”.